A Model Unavailability Perspective of Existing Nigerian Township Electricity Distribution - Melodi Adegoke Oladipo; Temikotan Kehinde Olusesan (Institute of Advanced Engineering and Science, 2017)
The study aimed to investigate and obtain model values of system unavailability and cost of energy not supplied in existing Nigerian township electricity distributions using a robust representative system. Outage data was obtained from system records for analysis using frequency distribution statistics to identify the causes of outages, and the contribution of each cause of outage to the overall system outage. The cost of energy not supplied (CENS) due to faults, was evaluated at a rate of NGN6 per kWHr. An analysis of the results shows that in a distribution feeder (and system) unavailability is mainly due to load shedding arising and faults; feeder unavailability involving load shedding is 0.25, and 0.1 without load shedding. Compared with standard UA value for well managed systems of less than or 0.01, the obtained unavailability values for a feeder show that downtime management was poor, and the corresponding cost – prohibitive. In view of the regular load shedding on the feeders and poor downtime management, this study recommends a need to obtain model loadflow perspective of township electricity distribution to ascertain load carrying capacity, and the application of distribution automation system or other effective strategies to mitigate downtime.